The Effect of Using English Video Clips with Pair Work Activity on Students’ Speaking Skil - Rosmawar Rosmawar (Universitas Syiah Kuala, 2018)
This research focused on the effect of using English video clip with pair work activity on students speaking skill at first grade students (VII-4) of MTsN 2 Banda Aceh. The purpose of this experimental quantitative research was to look at the effect of using English video clip with pair work activity on students speaking skill. The sample of this study was 25 students of class VII-4. In selecting the sample, the researcher used purposive sampling. In collecting the data, the researcher used test (pretest and postest) as the instrument and it was analyzed by using sample t-test. From the result of the study, it was found that the mean score of pre-test was 55,4 and the mean score of post-test was 81,2. It was clearly seen that the mean score of post-test was higher than the mean score of pre-test. Then, t-test was 4,534 and critical value in t-table (0,05) was 1,711, Meaning that t-score was higher than t-table (t-score = 4,534 t-table = 1,711). It means the altenative hypothesis (Ha) of this research was accepted and null hypothesis (Ho) was rejected. In conclusion, teaching English by using English video clip with pair work activity can give a significant effect toward the students’ speaking skill. Therefore, it is recommended that using English video clip with pair work activity can be alternative media used by the teacher in teaching English particularly in teaching speaking.